Impacts of Growth Strategies on Human Resources Policies - (:unkn) unknown (ELSEVIER SCIENCE BV, 2013)
One of the main motivation of businesses is growing by getting competitive advantage. New sales strategies, new product development trials, trying to create new investment areas, acquisitions and merges are some methods that are being used as a result of growth strategies. Whatever method is used, growth strategies have some impacts on businesses. Most of these impacts triger the need of change within the company. This study aims analysing changes on human resources strategies for the companies where growth strategies have been followed / still being followed in last 10 years.
Keywords: Growth; Human Resoiurces; Strategy; Change